Terror In topaz - Stuart, A. M., 1959- (Stuart, A. M., 1959- Harriet Gordon mystery, 2023)
The next instalment in the riveting HARRIET GORDON MYSTERIES. The chance to pursue a new opportunity takes Harriet and her brother Julian, to Kuala Lumpur, but death is waiting... Singapore 1910: Harriet Gordon has been dismissed from the job she loved and finds herself cast adrift. When her brother receives an invitation to visit a prestigious school in Kuala Lumpur, she and Julian decide to leave Singapore behind for a few days, but their pleasant visit takes a dark turn when a visitor to the school is shot dead on the front steps of the headmaster's bungalow. After being suspended from the Straits Settlements Police, Inspector Robert Curran has disappeared on a personal quest to find a missing girl but his suspension is not all it appears and he receives secretive orders to investigate the mysterious Topaz Club, which seems to be at the center of high-level corruption within the colonial government of Malaya. The uninvestigated death of a woman with links to the Topaz Club, brings Harriet and Curran together in a determination to shut down the notorious establishment for good. But a devious criminal stands in the way and it is going to take Harriet and Curran all their resources to bring justice for the victims of the Topaz Club and in doing so, find what it is they have been looking for in each other.